The rivers of milk and honey - Khan, Saniyasnain (Goodword Books New Delhi, 2007)
The Rivers of Milk and Honey is a delightful story that transports readers to a magical land where abundance and generosity thrive, illustrating the importance of gratitude and sharing the blessings of life with others.